Mechanisms and models for industry engagement in collaborative research in commercial fisheries - Baker, Matthew R.; Alverson, Robert; Christiansen, Ruth; Criddle, Keith; Eilertsen, Danny; Foy, Robert J.; Gauvin, John; Goodman, Scott E.; Habegger, Leigh; Harris, Bradley P.; Kimball, Nicole; Mercer, Anna Malek; et al. (Frontiers in Marine Science, 2023)
Data and insights from fishers are essential sources of information to advance understanding of fishery and ecosystem dynamics. Incorporating fisher and industry knowledge holds prospects for improving marine science and fisheries management. We address cooperative research in the context of collaboration between fishers, scientists, industries, universities, and agencies to develop applied research to understand marine ecosystems, inform fishery management, enhance sustainability, govern resource use, and investigate social-economic dynamics. We leverage the insights of more than 100 research scientists, fisheries managers, industry representatives, and fishers to outline actionable recommendations for effective approaches and mechanisms to integrate industry data, perspectives, and insights in fisheries science. We also highlight opportunities and address challenges and limitations to such collaboration.